2003
DOI: 10.1172/jci200318784
|View full text |Cite
|
Sign up to set email alerts
|

Small-intestinal dysfunction accompanies the complex endocrinopathy of human proprotein convertase 1 deficiency

Abstract: The biosynthesis of many secreted peptides involves limited endoproteolysis of larger, usually inactive, precursors to release the bioactive fragments. A family of serine endoproteases (proprotein convertases) that perform this processing function within the secretory pathway has been defined (1-3). Two members, proprotein convertases 1 and 2 (PC1 and PC2), which show expression confined to the regulated secretory pathway of neuroendocrine tissue, have been particularly closely studied. Although ex vivo experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 283 publications
(76 citation statements)
references
References 57 publications
(44 reference statements)
1
75
0
Order By: Relevance
“…An inactivating mutation in the gene encoding PC1 has been described in several subjects (122). Although loss of PC1 action might be predicted to include relative deficiency of bioactive GIP and GLP1, the glucose intolerance, intractable diarrhea, and malabsorption phenotype in these individuals probably obscures the potential importance of loss of incretin action in this setting.…”
Section: Gastrointestinal Disorders Affecting Glucose Homeostasismentioning
confidence: 99%
“…An inactivating mutation in the gene encoding PC1 has been described in several subjects (122). Although loss of PC1 action might be predicted to include relative deficiency of bioactive GIP and GLP1, the glucose intolerance, intractable diarrhea, and malabsorption phenotype in these individuals probably obscures the potential importance of loss of incretin action in this setting.…”
Section: Gastrointestinal Disorders Affecting Glucose Homeostasismentioning
confidence: 99%
“…14 Obesity can also result when, despite normal POMC transcription and translation, there is a problem with peptide processing, such as congenital deficiency of the processing enzyme prohormone convertase 1. 15 16 The receptors for the POMC cleavage product play a role in energy balance. The MC4 receptor is implicated in as much as 6% of severe early onset human obesity, 17 while a particular variant of the receptor is negatively associated with obesity.…”
Section: Central Regulationmentioning
confidence: 99%
“…Additionally, it has recently been shown that loss-of-function mutations of the G protein-coupled receptor, GPR54 , lead to nIHH in a few cases [7]. The other clinical entities associated with nIHH include leptin and leptin receptor defects [8], which are both characterized by severe childhood-onset obesity and hyperphagia, and prohormone convertase defects which present with childhood-onset obesity, hypoinsulinemia, and hypocortisolemia [9]. …”
Section: Introductionmentioning
confidence: 99%